2009
DOI: 10.1186/1550-2783-6-18
|View full text |Cite
|
Sign up to set email alerts
|

The effects of four weeks of creatine supplementation and high-intensity interval training on cardiorespiratory fitness: a randomized controlled trial

Abstract: BackgroundHigh-intensity interval training has been shown to be a time-efficient way to induce physiological adaptations similar to those of traditional endurance training. Creatine supplementation may enhance high-intensity interval training, leading to even greater physiological adaptations. The purpose of this study was to determine the effects of high-intensity interval training (HIIT) and creatine supplementation on cardiorespiratory fitness and endurance performance (maximal oxygen consumption (VO2PEAK),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…The "anaerobic threshold" in its various manifestations, for example, can be shown to correlate with endurance performance in a heterogeneous population, but may not be a good marker of performance in a more homogeneous population (Faude et al, 2009) and it can change in the opposite direction from performance changes in response to nutritional interventions. In spite of this, however, changes in this measure in response to a supplement intervention are sometimes used as evidence of a performance effect (Graef et al, 2009). Similarly, the Physical Working Capacity at Fatigue Threshold (PWC[FT]) is an indirect measure, based on electromyographic measurements made during an incremental test, that may or may not be relevant to exercise performance (DeVries et al, 2007).…”
Section: Potential Benefits Of Supplement Usementioning
confidence: 99%
“…The "anaerobic threshold" in its various manifestations, for example, can be shown to correlate with endurance performance in a heterogeneous population, but may not be a good marker of performance in a more homogeneous population (Faude et al, 2009) and it can change in the opposite direction from performance changes in response to nutritional interventions. In spite of this, however, changes in this measure in response to a supplement intervention are sometimes used as evidence of a performance effect (Graef et al, 2009). Similarly, the Physical Working Capacity at Fatigue Threshold (PWC[FT]) is an indirect measure, based on electromyographic measurements made during an incremental test, that may or may not be relevant to exercise performance (DeVries et al, 2007).…”
Section: Potential Benefits Of Supplement Usementioning
confidence: 99%
“…However, they examined different indicators of performance, with Graef, et al looking at ventilatory threshold (VT), VO2peak, and total work done (TWD), and Kendall, et al looking at critical power (CP) and anaerobic work capacity (AWC)Kendall et al, 2009). Graef, et al (2009) demonstrated improvement in VT, with no concurrent improvements to VO2peak or TWD. Considered to be an indicator of endurance performance, VT has been suggested to be a gauge for the ability of the cardiovascular system to adequately supply oxygen to the working muscles).…”
mentioning
confidence: 89%
“…Research is mixed regarding the efficacy of creatine supplementation on intermittent, high-intensity cycling performance. The majority of research suggests that creatine supplementation (5-25 g/day for 3-28 days) can improve total work and average/peak power performance and ventilatory threshold (3-6 cycling trials, 6-120 s of exercise/trial; 20-120 s of rest between trials) in young males and females [22][23][24][25][26][27][28][29][30][31]. However, a few studies have failed to observe the same benefits [32][33][34][35].…”
Section: Creatine Monohydratementioning
confidence: 99%
“…Currently, there are only three chronic HIIT studies (>4 weeks), which have examined the potential for creatine to augment training adaptations [23,24,33]. Creatine combined with 4 weeks of HIIT increased ventilatory threshold (VT) [23] and critical power in young males [24] compared to HIIT and placebo. Despite some favorable adaptive responses, there was no effect on whole-body oxygen uptake and time to exhaustion or total work capacity [23,24].…”
Section: Creatine Monohydratementioning
confidence: 99%
See 1 more Smart Citation